The Use Of Podcast To Improve The Speaking Competency of The Tenth Grade Students of SMA Negeri 1 Amlapura In Academic Year 2015/2016 - Dianithi, A.S. (Universitas Pendidikan Ganesha, 2017)
The objective of this research was to improve students’ English speaking competency by using podcast in teaching and learning. The subject of the research was the speaking competency of the tenth grade students of SMA Negeri 1 Amlapura, i.e. X MIA 1 class. The method used in this study was Classroom Action Research (CAR), conducted in two cycles. There were two kinds of data collected, the qualitative data were obtained from the questionnaires and observation checklist. The quantitative data were collected by conducting pre-test and post-test. The result of study showed that the main score of the students’ English speaking competency gained on the pre-test was 60.43, on the post-test 1 was 72.46 and on post-test 2 was 79.78 and 83.33% of students could pass the standard minimum score. It can be concluded that the students’ English speaking competency could be improved by using podcast in English teaching and learning.